War and Militarism in Modern Japan : Issues of History and Identity - Podoler, Guy, 1967-; Shillony, Ben-Ami (Global Oriental, 2009)
A considerable amount of writing has been published on Japan at war in the Second World War, and more recently scholars have been revisiting the Russo-Japanese War of 1904-5; whereas this volume strives to examine Japan's twentieth-century approach to war and militarism in a wider perspective, bringing hitherto unexamined new themes and subject-matter under scrutiny up to the present day. Among the topics covered are the February 26 Incident in Theatre and Film, Ethnicity and Gender in Wartime Japanese Revue Theatre, Military Festivals and the Japanese Self-Defence Forces, Major Trends in Japanese Treatment of POW's in Modern Times, and Japan's 'Tug of War'after the Russian War. Published to mark the distinguished academic career of Ben-Ami Shillony, who retired in 2006, this volume also offers valuable new insights into the theme of the Japanese and the Jews, including the Story and Myth of Anne Frank and Sadako Sasaki, the involvement of Jewish scientists in the making of the atomic bomb, and Japan's Jewish Policy in the late 1930's.